Navigating learning through catastrophic calamities: A phenomenological study - Gladys Andales; Teresita Sarile; Suzette Elladora; Fitzgerald Kintanar; Ariel Ramos (Journal of Science and Education)
This study examined the lived experiences of technology and livelihood learners while navigating in the learning process despite the calamities like COVID-19 pandemic and typhoon Odette.  Data were gathered from in-depth interview with participants, focus group discussions, and key informant interview through the interview guide. Transcripts were analyzed using Colaizzi’s method, wherein meanings are formulated through sorted codes, categories, and themes.  Findings revealed three emerging themes on participants’ difficult and challenging experiences which include, uphill battles in learning, learning opportunities, and rise to the challenges.  Meanwhile, two themes were found for the underlying effects of these experiences including, role acceptance and psychosocial discomfort.  Furthermore, three themes were identified for learners’ responses to the challenges in learning process, including actions towards learning, coping amidst adversities, and pillars of strength.  These experiences provided concepts to educators to improve teaching and becoming flexible in designing lessons and learning tasks guided with the learning continuity model mainly designed to teach in the midst of crises. Hence, the Department of Education may spearhead community assessment while in curriculum development to suffice the needs of the learning community and may guide division and school offices in the implementation of their localized and contextualized learning continuity plans.